Preparation, characterization and electrical properties of polyacrylonitrile/huntite composites - DUMLUDAĞ, FATİH; KAHRAMAN, MEMET VEZİR; MADAKBAŞ, SEYFULLAH (SPRINGER, 2014)
We focused on polyacrylonitrile (PAN)/huntite composites to reinforce the polymer prepared by adding different percentages (wt%) of huntite to PAN. The composites were characterized using thermogravimetric analysis, differential scanning calorimetry, fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy techniques. It was clearly seen that the composites of PAN/huntite have better thermal stability than pure PAN. The effect of the huntite adding to Polyacrylonitrile (PAN) on dc conductivity and dielectric constant was also investigated. Dc conductivity values were increased with increasing temperature. Activation energy values were calculated depending on huntite contents in PAN. Relative dielectric constant values varied in the range of 16.5-21.2 at room temperature at 100 kHz frequency depending on huntite concentrations. All the electrical measurements were performed in dark and vacuum ambient between the temperatures of 295 and 523 K. Dielectric measurements were performed in the frequency range of 40 Hz-100 kHz.
Keywords: Polyacrylonitrile; Huntite; Composites; Conductivity; Dielectric constant; FLAME-RETARDANT; MECHANICAL-PROPERTIES; HYDROMAGNESITE; BEHAVIOR; HUNTITE; NANOCOMPOSITES; FILLER